Effects of Urtica dioica supplementation on blood lipids, hepatic enzymes and nitric oxide levels in type 2 diabetic patients: A double blind, randomized clinical trial - Alidad Amiri Behzadi; Hamid Kalalian-Moghaddam; Amirhossein Ahmadi (Mashhad University of Medical Sciences, 2016)
Objective: Oxidative stress plays an important role in the development of diabetic complications including metabolic abnormality-induced diabetic micro-vascular and macro-vascular complications. Urtica dioica L. (U. dioica) has been traditionally used in Iranian medicine as an herbal remedy for hypoglycemic or due to its anti-inflammatory properties. The aim of the present study was to evaluate the effects of hydro-alcoholic extract of U. dioica on blood lipids, hepatic enzymes and nitric oxide levels in patients with type 2 diabetes mellitus. Materials and Methods: 50 women with type 2 diabetes participated in this study and were randomly divided into two groups namely, control and intervention groups. Control group received placebo and intervention group received hydro-alcoholic extract of U. dioica. Before and after 8 weeks of continuous treatment, some biochemical serum levels including FPG, TG, SGPT, SGOT, HDL, LDL, SOD and NO were measured. Results: The results indicated that after 8 weeks, in the intervention group, FPG, TG, and SGPT levels significantly decreased and HDL, NO and SOD levels significantly increased as compared to the control group. Conclusion: Our results encourage the use of hydro-alcoholic extract of U. dioica as an antioxidant agent for additional therapy of diabetes as hydro-alcoholic extract of U. dioica may decrease risk factors of cardiovascular incidence and other complications in patients with diabetes mellitus.